Eksplorasi Konsep Matematika pada Eduwisata Taman Jam Gadang untuk Pembelajaran Matematika Siswa SD - M. Imamuddin; Isnaniah Isnaniah (AR-RIAYAH : Jurnal Pendidikan Dasar, 2023)
Eduwisata jam gadang park, is a historic and interesting tourist spot, especially its beauty. Jam gadang park is one of the eduwisata found in the city of Bukittinggi. In addition to enjoying its beauty, this eduwisata can be used as a learning resource for students, especially elementary school students in the city of Bukittinggi. The purpose of this study was to explore the mathematical concepts that exist in the edu-tourism park jam gadang and then used as a learning resource for elementary school students. This type of research is qualitative with an ethnographic approach. Data were obtained by researchers through observation, interviews and documentation. The results of the exploration of the mathematical concepts of eduwisata taman jam gadang include; the concept of circle, square, rectangle, triangle, rhombus, clock number, and purchase price, selling price, profit and loss (social arithmetic). The mathematical concepts in this edu-tourism park can be used by teachers as a source of learning mathematics for elementary school students. The use of eduwisata jam gadang park as a learning resource can foster students' love of mathematics and local culture.